In vivo dosimetry with an inorganic scintillation detector during multi-channel vaginal cylinder pulsed dose-rate brachytherapy: Dosimetry for pulsed dose-rate brachytherapy - Peter D. Georgi; Søren K. Nielsen; Anders T. Hansen; Harald Spejlborg; Susanne Rylander; Jacob Lindegaard; Simon Buus; Christian Wulff; Primoz Petric; Kari Tanderup; Jacob G. Johansen (Physics and Imaging in Radiation Oncology)
Background and purpose: In vivo dosimetry is not standard in brachytherapy and some errors go undetected. The aim of this study was to evaluate the accuracy of multi-channel vaginal cylinder pulsed dose-rate brachytherapy using in vivo dosimetry. Materials and methods: In vivo dosimetry data was collected during the years 2019–2022 for 22 patients (32 fractions) receiving multi-channel cylinder pulsed dose-rate brachytherapy. An inorganic scintillation detector was inserted in a cylinder channel. Each fraction was analysed as independent data sets. In vivo dosimetry-based source-tracking was used to determine the relative source-to-detector position. Measured dose was compared to planned and re-calculated source-tracking based doses. Assuming no change in organ and applicator geometry throughout treatment, the planned and source-tracking based dose distributions were compared in select volumes via γ-index analysis and dose-volume-histograms. Results: The mean ± SD planned vs. measured dose deviations in the first pulse were 0.8 ± 5.9 %. In 31/32 fractions the deviation was within the combined in vivo dosimetry uncertainty (averaging 9.7 %, k = 2) and planning dose calculation uncertainty (1.6 %, k = 2). The dwell-position offsets were < 2 mm for 88 % of channels, with the largest being 5.1 mm (4.0 mm uncertainty, k = 2). 3 %/2 mm γ pass-rates averaged 97.0 % (clinical target volume (CTV)), 100.0 % (rectum), 99.9 % (bladder). The mean ± SD deviation was −1.1 ± 2.9 % for CTV D98, and −0.2 ± 0.9 % and −1.2 ± 2.5 %, for bladder and rectum D2cm3 respectively, indicating good agreement between intended and delivered dose. Conclusions: In vivo dosimetry verified accurate and stable dose delivery in multi-channel vaginal cylinder based pulsed dose-rate brachytherapy.